Germination substrate, temperature and post-seminal development of Dalbergia nigra seeds - Andrade, Antônio Carlos Silva de; Pereira, Tânia Sampaio; Fernandes, Marina de Jesus; Cruz, Ana Paula Martins; Carvalho, Amanda Silva da Rosa (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to define the germination substrate of Dalbergia nigra (Vell.) Fr. All. Ex Benth (jacarandá-da-bahia), to evaluate the most appropriate temperature for its seeds germination, and to study its post-seminal morphology, showing normal and abnormal seedlings patterns. Seeds were sowed on filter paper, towel paper and vermiculite, using the constant temperatures of 20, 25, 30 and 35°C as well as alternate temperatures of 20–30°C and 20–35°C. The statistical design was completely randomized (6x3) with 50 seeds sowed in four replications in which the following parameters were analyzed: normal germination (normal seedlings) percentage and speed emergence index. The best results were obtained for temperatures of 25°C and 20–30°C in vermiculite and towel paper substrates. Normal seedlings were classified as faneroepigeal germination type.